Damien Parer: “The Gamest Man Alive” - Anna Efstathiadou (Close Encounters in War Journal)
Damien Parer is one of the official Second World War photographers and cameramen of the Australian Department of Information (DoI). Parer is remembered for his superb footage of soldiers in action and his ability to be on the right ridge to capture shots when bombs and shells were falling. Although his work was widely used in the form of newsreels or stills in Australian cinemas, newspapers and magazines, far less attention is given to his writings. A product of his time, Parer carried in his work practices of intellectual and artistic activity and personal emotions, beliefs and values. This article uses Parer’s personal published and un-published material to explore his account of the highs and lows of the war abroad, his rapport with and admiration for the Australian Imperial Force (AIF) infantry men he filmed, and his conviction that a war photographer’s place was with the frontline troops. Through his first experience of bombing of civilian populations in the town of Ellason in Greece to the Middle Eastern desert and the jungle war in New Guinea, Parer remained faithful to his mission: to provide, as an official war photographer/cameraman, a record of the Australians at war as dictated by DoI, and through his writings, his own views on war cinematography and photography. This article argues that the relationship between Parer’s writing and imagery, initially relying on the traditional war rhetoric, transforms through his personal frontline war experience that blurs the line between life and death and intensifies his admiration for the resilient and resolute Australian troops.